(untitled) (American Journal of Islam and Society, 2011)
The Islamic Context of the Thousand and One Nights by Muhsin J. al-Musawi contains seven chapters, an introduction, and a conclusion. It addresses the Islamic factor in global times, the unifying Islamic factor, the age of the Muslim empire, and the burgeoning of a text. It also examines the role of the public, non-religious displacements in popular tradition, namely, the duality between Islam and culture—as well as the public role in narrative theorizations, that is, the impact of literary criticism. Finally, the author explores Scheherazade’s nonverbal narratives in religious contexts, demonstrating the underlying Islamic character of the work. Musawi’s recent work is a most welcome and long-needed addition to scholarship in the field of Arabic literature. Well-written and well-researched by one of the senior scholars on the subject, The Islamic Context demonstrates how the Thousand and One Nights operate within the parameters of the Islamic faith. A portrait of life in all its aspects, the work would never have reached us had it not been the product of a strong Islamic literary and cultural climate. Although rife with erotic escapades, sexual sins rarely go unpunished in the work. Despite all the morally deviant behavior displayed in the work, many of its tales are cautionary; they communicate ethical messages and promote the good and forbid the wrong through warnings grounded in Islamic law. While there is no shortage of sex in a multiracial, multilingual, and multicultural society, much of the merrymaking is motivated by love, instead of lust ...